Effect of azithromycin on fetal development in rats - Elkomy, Ashraf; M. Kandeil, Asmaa; Abo-Salem, Mohamed; A. Hassan, Wedad; Aboubakr, Mohamed; A. Elhemiely, Alzahraa (International Journal of Pharmacology and Toxicology, 2018)
This study was designed to evaluate the potential risks of the Azithromycin administration on fetuses. Therefore pregnant rats were received Azithromycin orally (90 and 180 mg/kg b.wt, daily) from sixth day until the fifteenth day of gestation. At 20th day of gestation female sacrificed; abortion, fetal resorptions, visceral examination, skeletal examination, Oxidative stress markers and histopathological examination for fetuses were recorded. Azithromycin caused abortion, fetal resorptions, growth retardation, hematoma and paralysis of limbs. Also caused cerebral dilatation, microcephaly, perforation of hard palate and hemorrhage around internal organs. By skeletal examination; weak and incomplete ossification were observed in bones .Biochemical studies showed that Azithromycin administration resulted in decreased glutathione reduced but increased malonaldahyde compared to control groups. Fetal kidney revealed degeneration and necrosis in the tubular lining epithelium and fibrosis in between the atrophied renal tubules. This study supports and proofs the potential risks of the azithromycin administration on fetuses.Â Â